Association of prenatal and childhood PBDE exposure with timing of puberty in boys and girls. (March 2017) - Harley, Kim G.; Rauch, Stephen A.; Chevrier, Jonathan; Kogut, Katherine; Parra, Kimberly L.; Trujillo, Celina; Lustig, Robert H.; Greenspan, Louise C.; Sjödin, Andreas; Bradman, Asa; Eskenazi, Brenda
Abstract: Background: Polybrominated diphenyl ether (PBDE) flame retardants are endocrine-disrupting chemicals that exhibit estrogenic and androgenic properties and may affect pubertal timing. Methods: Study subjects were participants between 1999 and 2013 in the Center for the Health Assessment of Mothers and Children of Salinas (CHAMACOS), a longitudinal cohort study of predominantly Mexican origin families in Northern California. We measured serum concentrations of four PBDEs (BDE-47, -99, -100, -153) in blood collected from mothers during pregnancy ( N  = 263) and their children at age 9 years ( N  = 522). We determined timing of pubertal onset in 309 boys and 314 girls using clinical Tanner staging every 9 months between 9 and 13 years of age, and timing of menarche by self-report. We used Poisson regression for relative risk (RR) of earlier puberty and parametric survival analysis for time ratios (TR) of pubertal milestones. Results: Prenatal concentrations of all 4 congeners and ƩPBDEs were associated with later menarche in girls (RRearlier menarche  = 0.5, 95% confidence interval (CI): 0.3, 0.9 for ƩPBDEs) but earlier pubic hair development in boys (RRearlier pubarche  = 2.0, 95% CI: 1.3, 3.3 for ƩPBDEs). No associations were seen between prenatal exposure and girls' breast or pubic hair development or boys' genital development. Childhood PBDE exposure was not associated with any measure of pubertal timing, except for an association of BDE-153 with later menarche. Conclusions: We found that prenatal PBDE exposure was associated with later menarche in girls but earlier pubarche in boys, suggesting opposite pubertal effects in girls and boys. Highlights: PBDE flame retardant exposure was associated with later age at menarche in girls. PBDEs were associated with later onset of puberty in normal weight girls. PBDE flame retardant exposure was associated with earlier onset of puberty in boys.